Efficacy of cyclosporin in severe ulcerative colitis attack - Ahmet DANALIOĞLU; Sabahattin KAYMAKOĞLU; Zeynel MUNGAN; Çetin KARACA; Kadir DEMİR and Ziyaettin DURAKOĞLU and Fatih BEŞIŞIK and Güngör BOZTAŞ and Yılmaz ÇAKALOĞLU and Atilla ÖKTEN (Turkish Journal of Gastroenterology, 2019)
-